Comparison on microstrip patch antenna modules and rectifier modules for RF energy harvesting - Sangaran, Manee; Ramasamy, Agileswari; Norashidah, Md Din; Devi, K. K. A. (Asian Research Publishing Network, 2016)
Electromagnetic energy harvesting holds a promising future as an alternative energy in order to power low power devices. RF energy harvesting systems has been carried out by many researches and efforts have been put into converting RF into usable DC. This paper is a comprehensive review paper which covers the antenna modules and rectifier modules which are being utilized in RF energy harvesting systems over the years. Both the antenna modules and rectifier modules are put into comparison and critically analysed. From the comparisons made, the gaps and challenges are further discussed in detail.